Factors affecting farmers’ adoption of natural farming technologies in New Albay, Maragusan, Compostela Valley, Philippines - Lamban, R.; dela Cerna, A.; Montiflor, M.; Bacus, R.; Concepcion, S.; Batt, Peter; Murray-Prior, Roy (International Society of Horticultural Science, 2011)
In the Philippines, the sustainability of natural resources and the profitability of farming has become a major concern for smallholder farmers. To address these concerns, government agencies and the private sector are delivering workshops on natural farming technologies to farmers. Training includes the preparation of different concoctions such as indigenous micro-organisms (IMO), fermented fruit juice (FFJ) and fermented plant juice (FPJ), fish amino acid (FAA), oriental herbal juice (OHN) and calcium phosphate (Caphos). Other natural farm technologies include vermiculture. The products from the training are applied to the farmer’s own farms with any surplus products sold to other farmers. In Maragusan, Compostela Valley, Philippines, a group of smallholder farmers have successfully produced organic fertilizers as a result of the training provided to them. Initially, while training was provided to the group to facilitate the marketing of the fresh vegetable crops they produced, the skills learnt were readily transferable. This study discusses the development of the New Albay cluster and factors leading to its decline as a marketing cluster. This study will also explore the costs and returns associated with the application of organic fertilizer to vegetable crops in comparison to conventional farming practices. Results show that the cost of production arising from the use of natural farming technologies is lower than conventional farming.